ANALISIS AKUMULASI MODAL MANUSIA DENGAN TINGKAT PARTISIPASI ANGKATAN KERJA DAN TINGKAT PARTISIPASI SEKOLAH UNTUK PENINGKATAN DAYA SAING DAERAH Studi Kasus Di Propinsi Jawa Timur) - David Sukardi Kodrat (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
Based on structure of employment status in Province of East Jawa City Area 2005, labor force participation rate in each city area is from 48.70 percent to 53.98 percent, highest in Surabaya City and lowest in Probolinggo City. School participation rate status never/not yet attended shool at most found in Probolinggo City about 11.28 percent and smallest amount in Surabaya City about 3.33 percent. Status attending school at most found in Malang City about 25.98 percent and smallest amount in Probolinggo City about 16.99 percent and status anttending school anymore at most in Mojekerto City about 78.99 percent and smallest amount in Malang City about 70.14 percent. Based on this condition, it is needed policy for increasing labor force participation rate and school participation rate with: (1) determine of special skill is needed, (2) determine of special training to increase skill and (3) determine of institution for special training support. Education will increase the opportunity to get a job or to make a new business and society who possess quality in human capital stock.